Emergency Surgery for Acute Mitral Valve Obstruction Resulting From Rapidly enlarging Left Atrial Myxoma - Alam, M Badrul; Quader, SA; Rahim, AM Asif; Bari, M Sajedul; Khan, ZH; Hassan, Muhammed K (Cardiovascular Journal, 2016)
Left atrial myxomas are benign, slow-growing primary cardiac tumors. They present with gradual onset of one or more of a triad of obstructive, embolic, or constitutional symptoms. Echocardiography aids in the detailed preoperative and intraoperative evaluation of the myxoma for surgical strategy planning. We describe a case of interstitial hemorrhage in a left atrial myxoma leading to rapid expansion of the tumor with features of acute, mitral valve obstruction. Echocardiography showed a cystic area in the left atrial tumor that corresponded to an area of recent hemorrhage confirmed on surgical removal. A 42 yrs old housewife presented with severe dyspnoea, cough and chest pain for 7 days, after detail evaluation she was diagnosed as a case of left atrial myxoma with heart failure. Subsequently she underwent emergency open heart surgery under cardiopulmonary bypass; removal of a huge LA myxoma was done, and recovered uneventfully. Cardiovasc. j. 2016; 8(2): 155-157